Practical active and passive recovery strategies for soccer players - Rey, E.; Padron-Cabo, A.; Barcala-Furelos, R.; Casamichana, D.; Romo-Perez, V. (Strength and Conditioning Journal, 2018)
As a result of training and competition load in soccer, the majority of the body's physiological systems are stressed. To accelerate the recovery process and enhance performance in soccer, different postexercise recovery modes have been suggested and are broadly classified into 2 categories: active recovery or passive recovery. Despite the popularity, there is a lack of scientific evidence for the validity of these recovery interventions. This review summarizes the evidence base for using active recovery, cold water immersion, whole-body vibration, neuromuscular electrical stimulation, and compression garments, as exercise recovery aids in soccer, and where possible, provides practical recommendations regarding usage.